Pseudomembranous colitis (Journal of Pathology of Nepal, 2019)
Pseudomembranous colitis is an inflammatory condition of the colon that is most often a manifestation of Clostridium difficile infection. If laboratory testing and endoscopic finding for Clostridium difficile infection is negative, then other less common etiologies should be sought for to identify the correct diagnosis. Ischemic colitis, inflammatory bowel disease, medications, chemicals, vasculitis, and multiple infectious pathogens are responsible for non-clostridium difficile Pseudomembranous colitis.   Exposure history, chronic medical problems and a current medication list will aid in narrowing the differential diagnosis. Histology varies significantly with underlying etiology and can establish the diagnosis. Treatment is specific to the underlying etiology. The purpose of this review article is to aware clinicians and other healthcare professionals about various etiologies of pseudo membranous colitis along with its histological finding and treatment.